136:oral Optimising health benefit packages in the era of COVID-19: a case study from Pakistan. (28th April 2022) - Torres-Rueda, Sergio; Kitson, Nichola; Bozzani, Fiammetta; Sweeney, Sedona; Raza, Wajeeha; Shah, Mashal Murad; Naylor, Nichola; Pearson, Carl; Eggo, Rosalind; Quaife, Matthew; Procter, Simon; Huda, Maryam; et al.
Abstract : Objective: The health systems costs of COVID-19 are high in many countries, including Pakistan. Without increases in fiscal space, COVID-19 interventions are likely to displace other activities within the health system. We reflect on the inclusion of COVID-19 interventions in Pakistan's Essential Package of Health Services (EPHS) and, from a financial optimisation perspective, propose which interventions should be displaced to ensure the highest possible overall health utility within budgetary constraints. Methods: We estimated the costs of all 88 interventions currently included in the EPHS and collected published data on their cost-effectiveness. We also estimated total costs and cost-effectiveness of COVID-19 vaccination in Pakistan. We ranked all EPHS interventions and COVID-19 vaccination by cost-effectiveness, determining which interventions are comparatively least cost-effective and, in the absence of additional funding, no longer affordable. Results: The EPHS assumes a spending per capita of US$12.96, averting 40.36 million disability-adjusted life years (DALYs). From a financial optimisation perspective, and assuming no additional funds, the introduction of a COVID-19 vaccine (US$3 per dose) should displace 8 interventions out of the EPHS, making the EPHS more cost-effective by averting 40.62 million DALYs. A US$6 dose should displace a further intervention and avert 40.56 million DALYs. A US$10 dose would partially fall out of the package, displacing four additional interventions. If health spending per capita decreased to US$8, a US$3 dose would still be affordable, but not US$6 or US$10 doses. Discussion: Cost-effectiveness is only one criterion considered when deciding which interventions are included in (or removed from) a health benefits package. While displacing certain interventions to create fiscal space for the COVID-19 vaccine may lead to a financially optimal scenario, doing so may be politically unfeasible or socially undesirable. We highlight the difficult trade-offs that health systems face in the era of COVID-19.